2016
DOI: 10.1002/2016gl069068
|View full text |Cite
|
Sign up to set email alerts
|

Responses of phytoplankton community to the input of different aerosols in the East China Sea

Abstract: Atmospheric deposition can affect marine phytoplankton by supplying macronutrients and trace elements. We conducted mesocosm experiments by adding aerosols with different composition (dominated by mineral dust, biomass burning and high Cu, and secondary aerosol, respectively) to the surface seawater of the East China Sea. Chlorophyll a concentrations were found to be the highest and lowest after adding aerosols containing the highest Fe and dissolved inorganic nitrogen (DIN), respectively. The relative abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Overall, the addition of haze particle supplies a considerable amount of N nutrients to relieve and even reverse the nutrient limitation of phytoplankton community. Although we cannot exclude the possible stimulation effects of other species, such as Cu (Meng et al, ), our results suggest a dominant role of nitrogen in aerosol in affecting phytoplankton in the primarily N‐limited NWPO.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Overall, the addition of haze particle supplies a considerable amount of N nutrients to relieve and even reverse the nutrient limitation of phytoplankton community. Although we cannot exclude the possible stimulation effects of other species, such as Cu (Meng et al, ), our results suggest a dominant role of nitrogen in aerosol in affecting phytoplankton in the primarily N‐limited NWPO.…”
Section: Discussionmentioning
confidence: 65%
“…For instance, due to the river input and atmospheric deposition, the ECS is regarded as the area characterized by relatively high levels of Cu in the surface seawater. However, microcosm incubation experiments conducted in the ECS showed that Cu in the aerosol might play a more important role in stimulating primary productivity than N, likely due to the high biomass in the ECS (Meng et al, ). Hence, combined with the modeling and above experimental results, we conclude that the deposition of haze particles in natural condition tends to cause a fertilization rather than inhibition effect on primary productivity over the NWPO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies showed that dissolved N from the added dust likely stimulated phytoplankton growth in the Yellow Sea (YS; Liu et al, 2013). Added Fe instead of other dissolved nutrients from atmospheric deposition played an important role in stimulating phytoplankton growth in the East China Sea (Meng et al, 2016). The complex responses of phytoplankton growth to dust deposition are worthy of investigation.…”
Section: Zhang Et Al: Phytoplankton Growth Response To Asian Dustmentioning
confidence: 99%
“…Atmospheric aerosols characterized by mineral dust or anthropogenic pollutants contain complicated chemical components, and their deposition to oceans can lead to complicated responses of phytoplankton (C. Paytan et al, 2009;Meng et al, 2016). The NCEI appears to have the advantage of revealing the possible mechanisms associated with the responses to some extent.…”
Section: Positive Effects Of Am Dust On Phytoplankton Growth In the Nmentioning
confidence: 99%